2020
DOI: 10.3847/2041-8213/abbfad
|View full text |Cite
|
Sign up to set email alerts
|

A Terrestrial-mass Rogue Planet Candidate Detected in the Shortest-timescale Microlensing Event

Abstract: Some low-mass planets are expected to be ejected from their parent planetary systems during early stages of planetary system formation. According to planet formation theories, such as the core accretion theory, typical masses of ejected planets should be between 0.3 and 1.0 M ⊕ . Although in practice such objects do not emit any light, they may be detected using gravitational microlensing via their light-bending gravity. Microlensing events due to terrestrial-mass rogue planets are expected to have extremely s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Only very few rogue planets are known [ 8 , 9 , 13 ] because they are so difficult to detect. Most exoplanets are discovered through their interactions with their parent star, which clearly is not an option for rogue planets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only very few rogue planets are known [ 8 , 9 , 13 ] because they are so difficult to detect. Most exoplanets are discovered through their interactions with their parent star, which clearly is not an option for rogue planets.…”
Section: Discussionmentioning
confidence: 99%
“…Life could have originated on such an Earth-type planet before it was ejected from its solar system, especially if it had a reducing atmosphere. In 2020 the first terrestrial-mass rogue planet candidate was claimed to be detected using microlensing [ 13 ], showing that Mars to Earth-sized mass rogue planets can be detected and characterized in principle using current technology. However, detections are extremely challenging, because Mars to Earth-sized planets are already difficult to identify when in orbit around a star.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As another example, Mróz et al (2020b) found μ rel = 10.6 mas yr −1 for OGLE-2016-BLG-1928, but a source proper motion very close to the mean of the proper motion distribution for bulge giants (i.e., μ rel = 5 ∼ 10 mas yr −1 ). Because of the source proper motion, they argue that the lens is more consistent with being a member of the disk.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, the OGLE and Korea Microlensing Telescope Network (KMTNet; Kim et al 2016) surveys have detected several strong FFP candidates with detections of finite-source effects (e.g., see Mróz et al 2018Mróz et al , 2019Mróz et al , 2020aMróz et al , 2020b. The KMTNet microlensing survey is particularly useful for FFP studies because of its continuous high-cadence observations, which enable both detection of short-timescale events and characterization of finite-source effects.…”
Section: Introductionmentioning
confidence: 99%